PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MOTOR OTOMOTIF SISWA KELAS X TKR SMK MUHAMMADIYAH CANGKRINGAN - Giri Andaru Sujoko; Rabiman Rabiman (Universitas Sarjanawiyata Tamansiswa, 2014)
The aims of this research are: (1) to know what the application of jigsaw learning approaches can enhance the student’s activeness especially on the motor automotive lesson; and (2) to know what the application of jigsaw learning approaches can enhance the academic result of student especially on the motor automotive lesson. The hypothesis of this research is a cooperative learning Jigsaw Model which can increase students activeness and results of the study on student motor automotive at X grade SMK Muhammadiyah Cangkringan.This research was conducted at SMK Muhammadiyah Cangkringan on February 17th until March 27th, 2014. The subjects in this study are students of X grade TKR B of 24 students. The type of this research was an action research (PTK). The data collection technique used observation sheets, test techniques, and documentation. Test instrument was implemented in class of X TKR SMK Muhammadiyah Cangkringan. The validity of question task was obtained from test results of product moment correlation. The analysis of cycle I, II, III was stated valid based on each item of 5 questions task of test. Reliability was obtained using cronbach alpha formula which was obtained based on the analysis of Interval coefficient cycles I which interpretation high level with 0.687, cycle II interpretation high level of 0.734, and cycle III high interpretation level 0.712. Data analysis techniques used by a percentage to the activeness of the study and quantitative analysis techniques which include the average absorbance values.The result of the analysis can be described as follows: (1) the learning model used the jigsaw can increase the activeness of the learners on learning subjects of automotive motor X grade SMK Muhammadiyah Cangkringan, Sleman. The average activeness of the students was on the cycle I of 72.52 rise to 76.02 on cycle II, and cycle III becomes 82.57; and (2) learning activity used jigsaw model can improve the learning results of the jigsaw students on automotive motor subjects of X grade SMK Muhammadiyah Cangkringan, Sleman. It can be seen from the average value of study on pre-test 67.33 rise on post-test cycle I became 74.75, on cycle II becomes 78.45 and cycle III became 83.75, whereas if viewed from the pre-absorbance test increased by 25% following the action on the cycle I of 62.5%, rise in cycle II becomes 79.17% and cycle III becomes 95.83%.